2002
DOI: 10.1053/eupc.2002.0238
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of ventricular function during permanent pacing from either right ventricular apex or outflow tract following AV-junctional ablation for atrial fibrillation

Abstract: No major differences were identified in systolic function between pacing sites. Some systolic parameters were better preserved with outflow tract pacing and diastolic function deteriorated subtly over time in both groups. Right ventricular pacing adversely affects left ventricular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 30 publications
1
63
0
5
Order By: Relevance
“…They concluded that these detrimental effects associated with RVS pacing might have resulted from the heterogeneity of the real pacing sites included under the umbrella of RVS pacing concept. These results are in accordance with other studies (Bourke et al, 2002;Dabrowska-Kugacka et al, 2009). Victor et al (Victor et al, 2006) found that in contrast to RVA pacing, RVS pacing preserved LVEF in patients with baseline LVEF ≤45%, but did not gain any advantage of LVEF in patients with baseline LVEF>45%.…”
Section: Authorssupporting
confidence: 83%
See 4 more Smart Citations
“…They concluded that these detrimental effects associated with RVS pacing might have resulted from the heterogeneity of the real pacing sites included under the umbrella of RVS pacing concept. These results are in accordance with other studies (Bourke et al, 2002;Dabrowska-Kugacka et al, 2009). Victor et al (Victor et al, 2006) found that in contrast to RVA pacing, RVS pacing preserved LVEF in patients with baseline LVEF ≤45%, but did not gain any advantage of LVEF in patients with baseline LVEF>45%.…”
Section: Authorssupporting
confidence: 83%
“…The RV septal pacing also resulted in shorter isovolumic relaxation than RV apical pacing (Yu et al, 2007), implicating better diastolic function that has been invasively demonstrated by Kolettis et al (Kolettis et al, 2000) at the cardiac catheterization laboratory. In fact despite the beneficial features of reducing electrical and mechanical dyssynchrony , different studies failed to demonstrate a positive effect on indices of LV structure and 85 function and did not confirm the above mentioned clinical outcomes, at least during the 3-18 months after implantation (Bourke et al, 2002;Victor et al, 2006;Kypta et al, 2008;Dabrowska-Kugacka et al, 2009;Gong et al, 2009;Cano et al, 2010) Kypta et al (Kypta et al, 2008) randomized 98 patients with atrioventricular block (AVblock) undergoing pacemaker implantation to positioning the ventricular lead in the high or mid septum (n =53) or in the apex (n = 45) of the right ventricle. The Changes of N-terminal pro-brain natriuetic peptide (BNP) levels, LVEF, and exercise capacity from baseline to 18 months were statistically not different between septal and apical stimulation.…”
Section: Authorsmentioning
confidence: 99%
See 3 more Smart Citations